A Application of Good Mining Practice at PT. Gunung Bale, Malang, East Java: Penerapan Good Mining Practice di PT. Gunung Bale, Malang, Jawa Timur - Gindang Rain Pratama (Media Ilmiah Teknik Lingkungan (MITL), 2022)
This study aims to determine the application of Good Mining Practice at PT. Bale Mountain. Mining activities at Gunung Bale consist of processes: Stripping and Top Soil Management, Mining Production Operations, Stock Pile Activities, Quality Control and Transportation to Consumers. The methodology used is a study of the application of Good Mining Practice. Data and information are processed and tabulated for later analysis descriptively and quantitatively. The results showed that the Mining Technical PT. Gunung Bale uses the open pit mining method with a Quarry mining system with a site hill type and a pit type. Mineral conservation is carried out using the method of calculating the volume of resources and reserves with the Triangular method using the Block model concept (software used is SURPAC 6.6.1). To prevent work accidents at the mine site, warning signs are installed and Personal Protective Equipment (PPE) and first aid kits are provided. Every time starting mining activities, a safety talk is held with the workers. Environmental management includes waste management, restoration and monitoring of water quality, handling of acid mine drainage, revegetation, and making a reclamation plan. The main mining infrastructure for road construction cuts around ±2 Ha. The total length of the road is 2,731 m. Processing and refining facilities are not located in the mining area.